Strategi Kepala Madrasah dalam Membangun Budaya Profesionalisme di Kalangan Guru - Muhammad Yunus Almator (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe and analyze the strategies employed by madrasah principals in fostering a culture of professionalism among teachers. Teacher professionalism serves as the primary pillar in enhancing the quality of education within madrasahs. A descriptive qualitative method was utilized for this research. The findings indicate that the principal's strategies include: (1) competency development through participation in Teacher Working Groups (KKG/MGMP), workshops, and seminars; (2) the implementation of consistent and clinical academic supervision; (3) providing motivation alongside fair reward and punishment systems; and (4) creating a conducive work environment based on religious values. The main obstacles identified are generally related to budget constraints and high administrative burdens for teachers. This study concludes that supportive and visionary leadership is crucial in determining the success of internalizing a professional culture within the madrasah environment.